Fermentation characteristics in hay from Cynodon and crop stubble treated with exogenous enzymes (Revista Ciência Agronômica, 2023)
The effect of treatment with xylanase and β-glucanase was evaluated for gas production and the ruminaldegradation of nutrients from the hay of Tifton 85 grass and the stubble of maize, sorghum, peanut, sunflower and sesamecrops. Two commercial fibrolytic enzymes were used (Dyadic xylanase PLUS - Xylanase; BrewZyme LP-β-glucanase), addedto the hay at doses of 7.5 units of endoglucanase and 0.46 units of xylanase per 500 mg/gDM, for the cellulase and xylanaseproducts respectively. The chemical composition of the hay was determined for no enzyme application and 24 hours afterenzyme treatment, and the in vitro gas production and in situ microbial degradation was estimated for dry matter, organicmatter, neutral detergent fibre and truly-degradable organic matter after 24 hours of incubation in the rumen. Enzyme treatmentof the hay from Tifton 85 grass and the stubble of maize, sorghum, sunflower, peanut and sesame crops with the exogenousfibrolytic enzymes β-glucanase and xylanase influences in vitro gas production, and the in situ degradation of dry matter,organic matter, neutral detergent fibre and truly-degradable organic matter in the rumen. This variation can be attributed todifferences in the chemical composition of the hay from the grass and the crop stubble, and to the different ways the enzymesact upon the cell wall.